Istawarta: Inovasi Media Pembelajaran Keterampilan Membaca Abad 21 Mahasiswa IAIN Madura dalam Mendukung SDGs - Sahril Hamdani; Mochamad Arifin Alatas; Albaburrahim, Albaburrahim (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This research is motivated by the development of technological times that are increasingly developing so that it is possible to use relevant learning media such as istawarta. Istawarta is a combination of the terms instagram and warta (news) which is an innovative learning media to improve students’ reading skills in the 21st century. The purpose of this study is to determine the use of istawarta in reading skills in IAIN Madura students and to determine the results of using istawarta as the latest innovation in learning media for reading skills of IAIN Madura students in the 21st century in supporting SDGs. This research uses descriptive qualitative method with data collection using observation, interview, documentation of IAIN Madura students who use istawarta. The main data source in this study comes from the istawarta of IAIN Madura students. The data analysis technique consists of data collection, data reduction, data presentation, and inference. The results of this study found 5 aspects in the reading skills of IAIN Madura students, namely sensory aspects, perceptual aspects, schemata aspects, thinking aspects, and affective aspects.